Enhancing efficiency in the control of artificial ground freezing for shaft construction: A case study of the Darasinsky potash mine - Mikhail Semin; Ivan Golovatyi; Lev Levin; Aleksei Pugin (Cleaner Engineering and Technology, 2024)
Artificial ground freezing during mine shaft construction is a costly endeavor. For effective decision-making in mining operations, it's essential to establish robust control over frozen soil conditions. This control holds paramount importance for ensuring mining safety. After considering the existing approaches to the control of artificial ground freezing, we conducted an analysis of their respective advantages and disadvantages. We introduced two novel principles for controlling the freezing process. These principles mark a substantial advancement from the previously proposed freeze-on-demand concept. Subsequently, we illustrated the practical implementation of these principles by sharing our experience in controlling artificial ground freezing during the construction of two potash mine shafts in the Republic of Belarus. One of the most noteworthy outcomes of this control is the development of innovative technical solutions aimed at enhancing energy efficiency and operational safety in shaft sinking. These solutions encompass interval-based permission for mining activities, facilitating earlier shaft sinking initiation. Another significant solution pertains to swiftly responding, devising, and implementing strategies to counteract groundwater infiltration within one of the frozen soil layers.